Social Reality and Modern Science (Philosophy and Progress, 2023)
As science developed many of the established facts tended to appear in a new light and were seen from an aspect that had earlier been ignored and as a rule new scientific theory originated from the clash of old theories and new facts. Not only that, science has reached at the highest peak of its development. Nevertheless, in this era of science and technology, it has not been fully harnessed to the welfare of humanity. The world today is in a serious crisis and humanity is being constantly threatened or misuse of science. Science ‘therefore’ is not only a blessing but also presents an unprecedented threat to the very existence of the human race. This unhappy consequence is not because of science itself but because of the antagonistic nature of social relationships. It is very clear that, social reality is distinct from biological relating or individual cognitive reality representing as it does a phenomenological level created through social interaction and transcending thereby individual motives and actions. We cannot hope to understand the role of a social scientist properly unless we have some idea of the reality with which he is supposed to be involved either passionately or dispassionately.Philosophy and Progress, Vol#71-72; No#1-2; Jan-Dec 2022 P 29-43